2023
DOI: 10.3390/pharmaceutics15010192
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Systems as a Strategy to Enhance the Stability of Oxytetracycline Hydrochloride Polymorphs in Solution

Abstract: In order to improve the stability of oxytetracycline hydrochloride, a polymorphic antibiotic set of novel binary systems were developed using β-cyclodextrin and amino acids with different acid-basic characteristics as ligands. The formation constants for each system containing β-cyclodextrin, L-aspartic acid, histidine and N-acetylcysteine were determined by Scott’s method and statistical studies. The structure of the binary systems with β-cyclodextrin and N-acetylcysteine was elucidated by NMR experiments. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Oxytetracycline hydrochloride is another broad-spectrum polymorphic tetracycline antibiotic with instability problems, including photodegradation, oxidative degradation, and hydrolysis. Bueno et al [ 49 ] surprisingly observed that binary systems obtained with βCD only demonstrated a reduction in the degradation rate of oxytetracycline hydrochloride form III in the aqueous solution, with an increase of 20 h in the half time when compared to free form. This revealed distinct interactions between the CD and each drug polymorph, which influence their stabilizing effects.…”
Section: Enhancement Of Drug Stability Induced By Cdsmentioning
confidence: 99%
“…Oxytetracycline hydrochloride is another broad-spectrum polymorphic tetracycline antibiotic with instability problems, including photodegradation, oxidative degradation, and hydrolysis. Bueno et al [ 49 ] surprisingly observed that binary systems obtained with βCD only demonstrated a reduction in the degradation rate of oxytetracycline hydrochloride form III in the aqueous solution, with an increase of 20 h in the half time when compared to free form. This revealed distinct interactions between the CD and each drug polymorph, which influence their stabilizing effects.…”
Section: Enhancement Of Drug Stability Induced By Cdsmentioning
confidence: 99%
“…In acidic conditions, colistin’s half-life remains extensive even at elevated temperatures, but it decreases notably under basic conditions [ 25 , 26 ]. Oxytetracycline’s stability is compromised by factors such as oxidation, hydrolysis, pH, temperature, and light exposure [ 27 ]. Data on the stability of oxytetracycline are notably scarce, presenting a challenge for comprehensive understanding.…”
Section: Introductionmentioning
confidence: 99%